2018
DOI: 10.1016/s1470-2045(17)30906-3
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar androgen therapy in men with metastatic castration-resistant prostate cancer after progression on enzalutamide: an open-label, phase 2, multicohort study

Abstract: Summary Background Prostate cancer that progresses after enzalutamide treatment is poorly responsive to further antiandrogen therapy, and paradoxically, rapid cycling between high and low serum testosterone concentrations (bipolar androgen therapy [BAT]) in this setting might induce tumour responses. We aimed to evaluate BAT in patients with metastatic castration-resistant prostate cancer that progressed after enzalutamide. Methods We did this single-centre, open-label, phase 2, multicohort study in the USA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
148
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(164 citation statements)
references
References 30 publications
3
148
0
1
Order By: Relevance
“…Androgen-repressed human PC cells were repressed by DHT in vitro in a concentration-dependent manner. 26 In addition, a phase II multicohort study by Teply et al 27 has shown that bipolar androgen therapy is clinically effective for CRPC. Therefore, it is tempting to speculate that the tumor-suppressive function of TRIM36 might be involved in the molecular mechanisms of bipolar androgen therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Androgen-repressed human PC cells were repressed by DHT in vitro in a concentration-dependent manner. 26 In addition, a phase II multicohort study by Teply et al 27 has shown that bipolar androgen therapy is clinically effective for CRPC. Therefore, it is tempting to speculate that the tumor-suppressive function of TRIM36 might be involved in the molecular mechanisms of bipolar androgen therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The exploitation of enhanced AR stability using high‐dose testosterone is addressed in a recent clinical trial for bipolar androgen therapy (BAT) of patients with Enz‐resistant CRPC. BAT, which is composed of applying supraphysiological androgen levels within repeated cycles of androgen deprivation and supplementation at high doses, re‐sensitized metastatic CRPC patients to Enz therapy . It is suggested that the sudden switch in the androgen levels provide less time for adaptive responses of AR‐signaling …”
Section: Regulation Of Ar Stability By Ar‐ligands and Through Therapymentioning
confidence: 99%
“…BAT, which is composed of applying supraphysiological androgen levels within repeated cycles of androgen deprivation and supplementation at high doses, re-sensitized metastatic CRPC patients to Enz therapy. 10 It is suggested that the sudden switch in the androgen levels provide less time for adaptive responses of AR-signaling. 10 In recent years, AR splice variants have come into prominence, primarily because of their ability to confer resistance to treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While this adaptive increase in AR facilitates their continuous growth in a castrate level of serum T (ie, <0.2 ng/mL or <0.7 nM), this paradoxically sensitizes CRPC cells to growth inhibition and death when these cancer cells are rapidly switched from a low castration level to a high (ie, >3 ng/mL or >10 nM) level of androgen. Indeed, this is the basis for clinical trials using Bipolar Androgen Therapy (ie, BAT), which cycles metastatic castration‐resistant patients rapidly between short episodic periods of pharmacologically high serum T back to castrate levels of low serum T …”
Section: Introductionmentioning
confidence: 99%